2022
DOI: 10.1007/s00221-022-06358-y
|View full text |Cite
|
Sign up to set email alerts
|

Consolidation of motor sequence learning eliminates susceptibility of SMAproper to TMS: a combined rTMS and cTBS study

Abstract: Earlier research suggested that after 210 practice trials, the supplementary motor area (SMA) is involved in executing all responses of familiar 6-key sequences in a discrete sequence production (DSP) task (Verwey, Lammens, and van Honk, 2002). This was indicated by slowing of each response 20 and 25 min after the SMA had been stimulated for 20 min using repetitive transcranial magnetic stimulation (rTMS). The present study used a similar approach to assess the effects of TMS to the more posterior SMAproper at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 62 publications
(94 reference statements)
0
0
0
Order By: Relevance
“…Additionally, a PET study suggests that the SMA is involved in the execution of previously learned sequences rather than in the acquisition of sequences (Honda et al 1998). In more recent studies, the SMA was found to be involved in the automatization of sequential movements (Shimizu et al 2020) and the consolidation of implicit sequence knowledge (Verwey et al 2022). We found that only three studies have targeted the SMA.…”
Section: 2' Inhibitory' and 'Facilitatory' Rtms Protocolsmentioning
confidence: 65%
See 1 more Smart Citation
“…Additionally, a PET study suggests that the SMA is involved in the execution of previously learned sequences rather than in the acquisition of sequences (Honda et al 1998). In more recent studies, the SMA was found to be involved in the automatization of sequential movements (Shimizu et al 2020) and the consolidation of implicit sequence knowledge (Verwey et al 2022). We found that only three studies have targeted the SMA.…”
Section: 2' Inhibitory' and 'Facilitatory' Rtms Protocolsmentioning
confidence: 65%
“…Different stimulation protocols (i.e., conventional rTMS vs. TBS), stimulation timings (i.e., before, during, or after learning), control stimulation (i.e., no control, sham stimulation, active control), and stimulation intensities were utilized in almost all studies. Although both repetitive stimulation techniques seem to modulate visuomotor sequence learning effectively, a recent study suggests that the conventional low-frequency rTMS has a greater inhibitory effect on motor sequence learning than cTBS (Glinski 2021;Verwey et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Counterbalancing sequences across practice and testing ensures that across participants familiar and unfamiliar sequences comprise the same sequence sets. Multiday practice and testing on a day after practice allow for studying consolidation of sequencing skill (Kim et al, 2016 ; Verwey et al, 2022a , b ; Wright et al, 2010 ). To determine the contribution of explicit knowledge, the practice or test phase in a DSP task is usually followed by an awareness test (see section “Preparing Longer Sequences”).…”
Section: The Discrete Sequence Production (Dsp) Taskmentioning
confidence: 99%
“…In addition to unveiling the underlying processing mechanisms, the DSP task has been used to address the effectiveness of procedures to boost motor sequence learning, like using mental practice (Sobierajewicz et al, 2016 ), and increasing contextual interference by randomly varying alternative sequences in a single block of trials (Random Practice, or RP), instead of practicing different sequences in separate blocks (Blocked Practice, or BP) 3 (Cross et al, 2007 ; Immink & Wright, 1998 ; Kim et al, 2018 ; Lin et al, 2012 , 2016 ; Verwey et al, 2022b ). In addition, DSP studies explored the learning benefits of noninvasive stimulation of brain areas like M1 and prefrontal areas using transcranial magnetic brain stimulation (TMS; Cohen et al, 2009 ; Kennerley et al, 2004 ; Ruitenberg et al, 2014 ; Verwey et al, 2022a ) and transcranial direct current stimulation (tDCS; Greeley et al, 2020 , 2022 ; Kim et al, 2020 , 2021 ; Kim & Wright, 2020 ; Sobierajewicz et al, 2019 ; Waters-Metenier et al, 2014 ).…”
Section: The Discrete Sequence Production (Dsp) Taskmentioning
confidence: 99%
See 1 more Smart Citation